Assessing Consumer Emotional Responses in the Presence and Absence of Critical Quality Attributes: A Case Study with Chicken Eggs - Wisdom Wardy (2018)
© 2015 Institute of Food Technologists®. Effects of attribute presence and absence on the emotional profile and consumer acceptability of products with varying qualities were assessed using eggs as an example. An online survey (n = 320) was used to evaluate emotional responses and acceptability to 5 types of egg quality attributes: intrinsic, aesthetic, extrinsic, expediency, and wholesome/safety, for both present and absent conditions. Attribute absence rather than presence evoked greater consumer discriminating emotions associated with eggs. Mean emotion intensity elicited by the presence of all quality attributes ranged from 1.67 (intrinsic; guilty) to 4.05 (wholesome; good) versus 2.01 (wholesome; satisfied) to 3.29 (wholesome; disgusted) when absent. Key positive emotions elicited by presence of attributes were active, calm, good, interested, happy, safe, and satisfied; while dominant negative emotions elicited by absence of attributes included disgusted and worried. Wholesome quality (constituted by egg freshness, "packing/best-before-date" and absence of visible cracks) exhibited the highest liking (7.65) and emotion intensities, while the emotional responses to both the presence and absence of intrinsic quality (constituted by nutrient-fortified egg, organic egg, and USDA-certified farm egg) were similar, reflecting their dynamic effects on emotions. Emotions and acceptability were more correlated for attribute absence than presence; and good, happy, and satisfied emotions were strongly related to egg acceptability (r ≥ 0.6). Egg product/packaging design can be oriented toward emphasizing wholesome and expedient attributes, since they enhance good, safe, and satisfied emotions, while minimizing disgust, worry, and boredom. The use of emotional responses and hedonic testing regarding attribute presence and absence would allow for improved selection of attributes critical to consumer acceptance of products. Practical Application: Assessing effects of attribute presence compared with absence on food-evoked emotions may offer valuable insights for differentiation of competing or otherwise similar products. Affective consumer responses to food products with varying sensory and quality attributes are influenced by several factors including psychographics, demographics, product category, and test design. In this study, a scenario is depicted where product developers can identify critical product features based on emotional assessment of products with and without quality attributes. This study is beneficial to product developers and the egg industry, as it identifies opportunities to better understand consumer needs, thereby, designing products destined for success in the marketplace.